Social and emotional relevance in face processing: happy faces of future interaction partners enhance the late positive potential - Bublatzky, Florian; Gerdes, Antje B. M.; White, Andrew J.; Riemer, Martin; Alpers, Georg W. (Frontiers in Human Neuroscience, 2014)
Human face perception is modulated by both emotional valence and social relevance, but their interaction has rarely been examined. Event-related brain potentials (ERP) to happy, neutral, and angry facial expressions with different degrees of social relevance were recorded. Social relevance was manipulated by presenting pictures of two specific face actors as future interaction partners (meet condition), whereas two other face actors remained non-relevant. As a further control condition all stimuli were presented without specific task instructions (passive viewing condition). A within-subject design (Facial Expression x Relevance x Task) was implemented, where randomly ordered face stimuli of four actors (2 women, from the KDEF) were presented for 1s to 26 participants (16 female). Results showed an augmented N170, early posterior negativity (EPN), and late positive potential (LPP) for emotional in contrast to neutral facial expressions. Of particular interest, face processing varied as a function of instructed social relevance. Whereas the meet condition was accompanied with unspecific effects regardless of relevance (P1, EPN), viewing potential interaction partners was associated with increased LPP amplitudes. The LPP was specifically enhanced for happy facial expressions of the future interaction partners. This underscores that social relevance can impact face processing already at an early stage of visual processing. These findings are discussed within the framework of motivated attention and face processing theories.